Analysis and Design of an Accounting Information System for Loan Distribution at the Employee Cooperative of the Republic of Indonesia Teachers' Association (PGRI) - Wulandari, Mayli; Anggionaldi, Muhammad (Jurnal Ragam Pengabdian, 2026)
The increasing demand for accurate financial management requires cooperatives to adopt integrated accounting information systems. The employee cooperative of the Indonesian Teachers Association in Arjawinangun still uses manual procedures for recording loans, installment payments, and financial reports, causing delays, data duplication, calculation errors, and limited access to timely information. This study aims to analyze the existing loan accounting information system and design a computerized system to improve operational effectiveness and reporting quality. Using a descriptive approach and the Waterfall development method, data were collected through observation, interviews, and documentation. The results show that the current manual system is inefficient in processing loan applications, verifying member data, managing installment transactions, and generating reports. The proposed system integrates member, loan, and installment data into a centralized database, automates calculations and report generation, and enables real-time monitoring. The design is expected to improve data accuracy, operational efficiency, internal control, and management decision-making, while supporting the digital transformation of cooperatives and serving as a reference for similar financial institutions.